The soft power of a First Lady—Constructing identities for First Ladies in the Chinese and American media. (December 2017) - Zhang, Lei
Abstract: Soft power has replaced hard power to become a significant channel for countries to further their agendas in international affairs. As one instrument of enhancing soft power, media discourse bears material effects on the world through its choices in the identity construction of First Ladies. Combining corpus-based methods with micro-level manual analysis of English news from Chinese and American news sources, a comparative analysis of how the American and Chinese media construct the identities of Peng Liyuan and Michelle Obama is carried out within the approach of critical discourse analysis. The choices of key words, naming strategies, transitivity and metaphors in these two media reveal their differences in balancing multiple and mixed identities of these two First Ladies, in spite of their similarities in foregrounding the respective First Lady's celebrity identity. This demonstrates different understandings of soft power in Chinese and American culture and how identity construction of the First Lady contributes to the promotion of their soft power.